Student Employment Models for Undergraduate Nurses and Midwives in Australia: A Scoping Review - David J. Lindsay RN, PhD; Tracey A. Ahern RN, PhD; Madelyn K. Pardon BPsych; Marie T. McAuliffe RM, PhD; Sam G. Rannard Grad Dip Inf Stud (SAGE Publishing, 2023)
Introduction Evidence has shown that throughout their undergraduate years, many nursing and midwifery students obtain paid employment in a wide variety of clinical and non-clinical positions. Across Australia, inconsistencies exist in the models of clinical employment available to these student groups. Previous Australian studies have described the employment of undergraduate nursing and midwifery students in regulated and unregulated clinical roles. No studies have reported on the various regulated roles available to both student nurses and midwives in Australia. The purpose of this scoping review is to identify and synthesize evidence related to nursing and/or midwifery students employed in regulated and unregulated clinical roles in Australia. Methods This scoping review utilized published recommendations for data screening, abstraction, and synthesis. One of the authors, a librarian, undertook systematic searches in CINAHL Complete (1937-present), Emcare on Ovid (1995-present), Scopus (1969-present), and Ovid MEDLINE(R) (including Epub Ahead of Print, In-Process, and In-Data-Review & Other Non-Indexed Citations, 1946-present). The initial searches were completed in April 2019 and repeated in March 2021 and May 2022 to identify any new literature. Manual searching of reference lists in the included papers was also undertaken, together with selected organizational websites. The extracted data included the lead author, date, title, study design, study sample and location, and key findings. Results From the 53 items retrieved, 23 peer-reviewed studies met the inclusion criteria and were included in the review. All items were published between 2011 and 2022. Only four of the studies focused upon student midwives. Undergraduate nursing and midwifery students in Australia obtain paid employment in a variety of regulated and unregulated clinical roles. Conclusion The literature reported here demonstrates that there are differing models, nomenclature, educational requirements, and pay scales in place for student employment in clinical roles across Australian states and territories.